Plasma extracellular vesicles modulate immune cell gene expression following myocardial infarction. (25th November 2020) - Akbar, N; Braithwaite, A; Lewe, C; Lemke, S; Alkhalil, M; Dragovic, R; Melling, G; Carter, D.R.F; Channon, K.M; Choudhury, R.P
Abstract: Background: Myocardial infarction (MI) induces activation of immune cells and alters their gene expression en route to the injured myocardium but the underlying mechanisms coordinating immune cell programming following MI remain unknown. Plasma extracellular vesicle (EV) numbers are elevated in MI, correlate with the extent of myocardial injury and mobilises immune cells from the splenic reserve to peripheral blood. Here, we describe the role of plasma EV-microRNAs (miRs) in the modulation of peripheral blood mononuclear cell (PBMC) transcriptomes post-MI. Methods: PBMCs were exposed to plasma EVs followed by whole transcriptome RNA-sequencing. Plasma EVs were isolated by size-exclusion chromatography and ultra-centrifugation (2 hours at 120, 000 x g) from patients presenting with ST-segment elevation MI (STEMI) (N=9) and non-STEMI (NSTEMI) (N=11) control patients. Plasma EVs were characterised by western blot and Nanoview for EV markers CD9 and CD63, transmission electron microscopy (TEM) for morphology and Nanoparticle Tracking Analysis for size and concentration. High sensitive C-reactive protein (hs-CRP) and PCSK9 were determined in plasma by ELISA and compared to plasma EV number using Pearson's correlation. Plasma EV-miRs were measured by Agilent microarray and miR-mRNA putative targets assessed by TargetScanHuman. Results: Plasma EVs were positive for EV markers CD9 and CD63, displayed typical EV morphology by TEM and had a heterogeneous size and concentration distribution profile as determined by Nanoparticle Tracking Analysis. Plasma EV number correlated significantly with hs-CRP at presentation (R 2 = 0.20 and P<0.05). miRNA array analysis revealed STEMI plasma-EVs contained significantly more miR-4487 (P<0.001), miR-6511b-5p (P<0.001), miR-4508 (P<0.001) vs NSTEMI control plasma-EVs at the time of injury. STEMI-plasma-EVs induced differential gene expression in PBMCs vs. NSTEMI-control-plasma-EVs. Gene set enrichment analysis (GSEA) showed STEMI-plasma-EVs upregulated pro-inflammatory pathways including: interferon-α (IFN-α) (P<0.01), IFN-γ (P<0.01), tumour necrosis factor-α (TNF-α) (P<0.01) and interleukin-6 (IL-6)-STAT3 signalling of the acute phase response (P<0.05). miR-4487 (P<0.001) and miR-6511-5p (P<0.05) predicted mRNA targets were significantly enriched in PBMC transcriptomes following treatment with STEMI plasma-EVs. Conclusions: Plasma EVs mediating immune cell transcriptional programming following MI by promoting inflammatory pathways in PBMCs is a novel finding. Targeting PBMCs with EVs may allow modulation of the immune response following myocardial injury, to perturb inflammatory immune mediated damage following ischaemic injury. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation Centre of Research Excellence Awards, British Heart Foundation Project Grant, Novo Nordisk Fonden the Tripartite Immunometabolism Consortium and Wellcome Institutional Strategic Support Fund (ISSF)